Low dose posaconazole delayed release tablets for fungal prophylaxis in lung transplant recipients. Issue 8 (15th June 2018) - Kozuch, Jade M.; Feist, Ashley; Yung, Gordon; Awdishu, Linda; Hays, Steven; Singer, Jonathan P.; Florez, Rebecca
Abstract: In November 2013, posaconazole delayed release (DR) tablets were approved by the FDA with the labeled dose of 300 mg daily for fungal prophylaxis. There are no studies demonstrating the appropriate dose in lung transplant recipients (LTR). We performed a 2‐center retrospective cohort study of LTR taking posaconazole DR tablets for prophylaxis between January 2014 and January 2017. Mean serum trough concentrations and percentage of measurements ≥0.7 mcg/mL were compared by daily dose. Forty‐nine subjects with 156 steady state serum posaconazole concentrations were included. There was a significant difference in percentage of first measured concentration ≥0.7 mcg/mL by initial daily dose ( P  = .04). The mean serum posaconazole concentration by dose was 0.9 (±0.42) mcg/mL for 100 mg daily, 1.66 (±0.91) mcg/mL for 200 mg daily, 2.39 (±1.49) mcg/mL for 300 mg daily, and 1.75 (±0.21) mcg/mL for 400 mg daily ( P  < .001). Mean concentrations were at goal in 63.3%, 96.9%, 94.9%, and 100% of subjects taking 100 mg, 200 mg, 300 mg, and 400 mg daily respectively ( P  = .04). Our results suggest that doses less than 300 mg daily of posaconazole DR tablets may be adequate to achieve target serum concentrations in LTR. Larger studies are needed to confirm these findings.